2015
DOI: 10.1007/s10802-015-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Can Callous-Unemotional Traits be Reliably Measured in Preschoolers?

Abstract: Callous-unemotional (CU) traits designate an important subgroup of antisocial individuals at risk for early-starting, severe, and persistent conduct problems, but this construct has received limited attention among young children. The current study evaluated the factor structure, psychometric properties, and validity of scores on a comprehensive measure of CU traits, the Inventory of Callous-Unemotional Traits (ICU), in relation to measures of antisocial/prosocial behavior and emotional processing, administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
125
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(165 citation statements)
references
References 65 publications
16
125
1
1
Order By: Relevance
“…Measures of CU behaviors assessed as young as age 3 also robustly predict concurrent and subsequent antisocial behavior. For example, CU behaviors were significantly related to a disruptive behavior disorder diagnosis among 3‐ to 4‐year‐olds and correlated with more teacher‐reported overt and relational aggression among 3‐ to 6‐year‐olds . Longitudinally, CU behaviors predicted teacher‐reported proactive aggression 9–12 months later in 2‐ to 5‐year‐olds .…”
Section: Early Childhood Cu Behaviors As a Precursor To Cu Traitsmentioning
confidence: 96%
“…Measures of CU behaviors assessed as young as age 3 also robustly predict concurrent and subsequent antisocial behavior. For example, CU behaviors were significantly related to a disruptive behavior disorder diagnosis among 3‐ to 4‐year‐olds and correlated with more teacher‐reported overt and relational aggression among 3‐ to 6‐year‐olds . Longitudinally, CU behaviors predicted teacher‐reported proactive aggression 9–12 months later in 2‐ to 5‐year‐olds .…”
Section: Early Childhood Cu Behaviors As a Precursor To Cu Traitsmentioning
confidence: 96%
“…Several studies have shown that child psychopathic traits can be observed at very young ages (Assary, Salekin, & Barker, ; Kimonis et al., ; Waller et al., ), and the traits have been shown to demonstrate stability. For instance, Waller et al., examined children from ages 2 to 4 years and found moderate stability.…”
Section: Early Measurement and Temporal Stability Of Psychopathic Dimmentioning
confidence: 99%
“…The uncaring factor is also consistently associated with empathy deficits (Hawes et al., ). Evidence of construct validity for the unemotional factor has been established with empathy and sensation‐seeking measures, yet this factor has not been consistently related to other behavioral correlates (Kimonis et al., ).…”
Section: Inventory Of Cu Traitsmentioning
confidence: 99%